Economic impacts at local level of major earthquakes in Costa Rica: Lessons from Limón 1991, Cinchona 2009,and Sámara 2012. - Quesada Román , Adolfo; Martínez Rojas, Natalia (Revista Geográfica de América Central., 2025)
This paper presents a comprehensive analysis of the economic impacts, by sector, of the three most recent major earthquakes in Costa Rica (Limón 1991, Cinchona 2009, and Sámara 2012). The study sheds light on the localized effects of seismic events and identifies the sectors and municipalities most affected by earthquake-induced economic disruption. Through a detailed examination of past earthquake data and their economic aftermath by national institutions, the study emphasizes the significance of preparedness and risk reduction strategies for regions prone to seismic activity. The research findings reveal that specific municipalities, notably Alajuela, Limón, and Sarchí, have consistently borne the brunt of earthquake-related economic impacts. These areas experienced disruptions across various sectors, impacting not only local economies but also national stability. The most severely affected sectors were electricity, housing, and agriculture, highlighting the critical role these sectors play in the country’s overall economic resilience. These results hold valuable implications for disaster risk reduction stakeholders in Costa Rica and other nations sharing similar seismic, geomorphological, and climatological conditions. The identification of municipalities and sectors canaid in the development of targeted mitigation strategies, policy formulation improvement, and resource allocation to enhance overall disaster preparedness at a local scale. Seismic activity will continue posing challenges worldwide, the insights from this study offers a roadmap for sustainable development and resilience building in earthquakeprone regions.